Description of the first species of gall wasp (Hym., Cynipidae: Cynipini) on Quercus grahamii (Fagaceae) - Pujade-Villar, Juli; Pérez-Torres, Betzabeth C.; Coombes, Allen J.; Aragón-García, Agustín; Rodríguez-Acosta, Maricela; López-Olguin, Jesús F.; Melika, George (Zootaxa, 2024)
A new species of oak gall wasp, Andricus coombesi Pujade-Villar & Pérez-Torres n. sp. from Mexico, known only from its asexual generation that induces galls on acorns of Quercus grahamii Benth., (section Lobatae) is described. Its presence causes the complete disappearance of the acorn. Diagnosis, distribution and biological data of the new species are given. Andricus coombesi Pujade-Villar & Pérez-Torres n. sp. represents the first gall wasp species mentioned from this host.